2020
DOI: 10.24815/jdab.v7i2.16597
|View full text |Cite
|
Sign up to set email alerts
|

Optimizing Zakat Collection in the Digital Era: Muzakki's perception

Abstract: This study aims to examine the determinants of zakat payers' (muzakki) interest to pay zakat through Zakat Management Organization (ZMO). The respondents were muzakki (Zakat payers) who paid their zakat on profession/income through ZMOs in Indonesia. The number of respondents is 100 muzakki who were selected randomly. Using the structural equation modelling (SEM) method, this study found that transparency of zakat management, ZMO promotions through public figure involvement, and the supporting regulation which… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0
6

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 31 publications
0
10
0
6
Order By: Relevance
“…Its paper also stated that the emergence of the internet has provided people with unrestricted access to knowledge. Despite that fact, Antonio et al (2020) found that zakat socialization through social media does not affect the muzzkaki's intention to pay zakat in the zakat institution.…”
Section: Existing Program Of Zakat Socialization and Educationmentioning
confidence: 85%
“…Its paper also stated that the emergence of the internet has provided people with unrestricted access to knowledge. Despite that fact, Antonio et al (2020) found that zakat socialization through social media does not affect the muzzkaki's intention to pay zakat in the zakat institution.…”
Section: Existing Program Of Zakat Socialization and Educationmentioning
confidence: 85%
“…Reinforced by research by Muhammad Syafi Antonio et al [28], which states that digital services and socialization of zakat through social media influence the interest of muzakki in paying zakat. The results of research by Syahputra [29], which states that digital zakat affects people's interest in paying zakat with the e-payment system providing convenience for the community in distributing Zakat.…”
Section: Zakat's Digital Influence On the Interest Of Zakatmentioning
confidence: 99%
“…Furthermore, zakat management organizations must ensure the transparency of their institutions, especially regarding the collection and distribution of zakat funds and the availability of methods for using zakat funds that are more attractive to muzakki. Muzakki's interest in paying zakat was influenced by transparency and accountability factors (Rahayu et al, 2019;Mukhibad et al, 2019;Ikhwanda dan Hudayati, 2019), socialization (Purnamasari and Firdaus, 2017), and service quality (Antonio et al, 2020).…”
Section: Empirical Studiesmentioning
confidence: 99%